The chemical composition and biological activities of essential oil from the aerial parts of Eryngium maritimum L. (Apiaceae) - Elkiran, Omer; Avsar, Cumhur; Veyisoglu, Aysel; Bagci, Eyup (Taylor & Francis Ltd, 2023)
This study aimed to describe the chemical composition of the Essential Oil (EO) of the aerial parts of E. maritimum, and verify its antimicrobial and antioxidant properties. The EO chemical characterization was simultaneously obtained by GC/FID and GC/MS. Thirty-one compounds corresponding to 93.3% of the EO were identified in the EO of E. maritimum. Spathulenol (22.0%), aromadendrene (18.3%), humulene epoxide (6.6%), and beta-humulene (4.8%) were the main compounds of the EO. The antimicrobial activities were determined against 3 gram-positive bacteria, 4 gram-negative bacteria, and 2 yeast species by using disc-diffusion and MIC techniques. EO showed a low effect (8-11 mm) against all tested bacteria and yeasts. Additionally, EO extract against Staphylococcus aureus ATCC 6538 and Shigella flexneri ATCC 12022 from tested microorganisms presented a MIC value at mu l/ml concentration. The antioxidant activity of the EO was determined as IC50=16.8 +/- 1.65 mu l/mL. To the best of our knowledge, this is the first report on the chemical composition and biological activities of E. maritimum EO in Turkey.
Keywords: Eryngium maritimum; essential oil; spathulenol; antimicrobial activity; antioxidant activity